A novel mechanism for nodular corrosion of Zircaloy-4 corroded in 773 K superheated steam. (September 2017) - Xie, Shijing; Zhou, Bangxin; Liang, Xue; Liu, Wenqing; Li, Hui; Li, Qiang; Yao, Meiyi; Zhang, Jinlong
Graphical abstract: Highlights: The corrosion resistance of Zircaloy-4 plate specimens corroded in 773 K/10.3 MPa superheated steam is anisotropic, The rolling surface (SN) mainly suffers uniform corrosion, but the surface perpendicular to transversal direction (ST) and the surface perpendicular to rolling direction (SR) mainly suffer nodular corrosion. The Sn segregation at the O/M interfaces where the crystallographic orientations of matrix grains are close to or is obvious, but there is nearly no Sn segregation at the O/M interfaces where the crystallographic orientations of matrix grains are close to (0001). A novel mechanism on nodular corrosion of Zircaloy-4 related to Sn segregation at O/M interface is proposed. The anisotropic corrosion resistance of Zircaloy-4 plate specimens is attributed to the anisotropy of Sn segregation at the O/M interfaces formed on SN, SR and ST surfaces with different grain orientations. Abstract: Corrosion resistance of Zircaloy-4 plate specimens in 773 K/10.3 MPa superheated steam is anisotropic. The rolling surface (SN ) mainly suffers uniform corrosion, while the surface perpendicular to transversal direction (ST ) and the surface perpendicular to rolling direction (SR ) mainly suffer nodular corrosion. A novel mechanism of nodular corrosion related to Sn segregation at the interface between oxide and matrix (O/M) is proposed. The anisotropic nodular corrosion results from the anisotropy of Sn segregation at the O/M interfaces formed on SN, SR and ST surfaces with different grain orientations. Finally, some reported results about nodular corrosion in zirconium alloys are discussed.